Collagen Hydrogel as Bio Interactive dressing for wound healing - Hema, G. S.; Ganesan, B.; Shyni, K.; Joshy, C. G.; Ninan, George; Mathew, Suseela (Fishery Technology, 2017)
In the present study, wound healing efficacy of the hydrogel prepared from fish skin collagen was evaluated in experimental full thickness wounds using albino rat model. The study demonstrated that within 2 weeks, the wound covered with gel were completely filled with new epithelium without any significant adverse reactions. The results clearly suggest that the hydrogel enhances re-epithelialization rather than a repair which was clear from the histopathology and biochemical analysis. There is significant increase in angiogenesis, collagen deposition, hexosamine content, epithelialization and wound contraction in hydrogel treated rats without inflammatory cells compared to the control group, indicating the tissue regeneration potential of fish collagen.